The Postural Control System in Individuals with Autism Spectrum Disorder: Insights from Exploring the Effects of Visual Information on Postural Control - Lim, Yi Huey (Curtin University, 2019)
The thesis examined the effects of static and dynamic visual information on postural control in individuals with autism spectrum disorder (ASD). The results suggest that the visual-motor mechanism adopted by ASD individuals to control posture is different from typically-developed individuals. Evidence of postural control impairments was also identified in ASD individuals. The findings advance the understanding of postural control in ASD and may guide the development of effective postural control interventions for ASD individuals.